On a class of third order neutral delay differential equations with piecewise constant argument - Garyfalos Papaschinopoulos (International Journal of Mathematics and Mathematical Sciences)
In this paper we study existence, uniqueness and asymptotic stability of the solutions of a class of third order neutral delay differential equations with piecewise constant argument.